Selective Harmonic Elimination Based on Newton-raphson Method for Cascaded H-bridge Multilevel Inverter - Wahidah Abd Halim; Tengku Noor Ariana Tengku Azam; Komathi Applasamy; Auzani Jidin (Institute of Advanced Engineering and Science, 2017)
Multilevel inverters are emerging as the new breed of power converter options for high power applications. They typically synthesis the staircase voltage waveform (from several dc sources) which reduced harmonic content. This paper presents a simple selective harmonic elimination (SHE) modulation for single-phase cascaded H-bridge (CHB) multilevel inverter. The optimum switching angle of the transcendental equations describing the fundamental and harmonic components is solved by means of the Newton-Raphson (NR) method. The proposed SHE scheme is performed through simulation using MATLAB/Simulink. This simulation results are then verified through experiment using Altera DE0-Nano field-programmable gate array (FPGA). The proposed SHE is efficient in eliminating the lowest-order harmonics and producing a higher quality output waveform with a better harmonic profile.